(untitled) (Research, Society and Development, 2020)
Tetanus is an infectious disease caused by the toxin of Clostridium tetani, a gram-positive anaerobic bacterium that affect domestic animals and humans. On February 17, 2019, veterinary medical care was requested at a property located in the city of Jataí, Goiás to attend the case of an undefined breed male horse of approximately 15 years of age, chestnut hair, weighing 400 kg. During the consultation, the main complaint was lameness and prolapse of third eyelid. At the clinical examination, the animal showed spasticity, rigid walking, distant hind limbs, third eyelid prolapse, hyperesthesia, extended neck, tail away from the body, mild dyspnea, intense sweating, distended nostrils and erect and immobile ears. Based on the physical examination of the animal, as well as the clinical signs presented, the final diagnosis of tetanus was established and therefore, the treatment was immediately instituted with intravenous anti-tetanus serum and antibiotic therapy. Hence, this paper aims to report a case of tetanus in equine, elucidating the main clinical signs and implemented treatment.